If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(3xx-9)=-234
We simplify the equation to the form, which is simple to understand
-6(3x-9)=-234
Reorder the terms in parentheses
+(-18x+54)=-234
Remove unnecessary parentheses
-18x+54=-234
We move all terms containing x to the left and all other terms to the right.
-18x=-234-54
We simplify left and right side of the equation.
-18x=-288
We divide both sides of the equation by -18 to get x.
x=16
| 6-2x-1=4+8-6x | | 4-4x=9-9x | | 2(x+4)=3(x-3) | | 1.7t-4.5=7.75 | | 9+3x=2-4x | | 10x+5y=35 | | 6z=3z-8+2z | | (50*45)/60+5= | | 3(4-x)=5+4x | | k/15=18 | | 5.1+1.9x=2.9x | | 3(3x+1)=8(x+1) | | 17-5x=3x+1 | | 2+3x=58 | | 2x-2+x=4+5 | | 18-4h=-10-4h | | 6x^2y^2-52xy^2-210y^2=0 | | 12-6x=9-7x | | 2x^2=4xs | | 2(w-3)+7=1-2w | | 4-x=x | | x^5+x^2+x=0 | | 8x+4=5(x+2) | | 9.40dm=hm | | X-2x=3x-20 | | 6(7+2x)-8x-(y+4)=12 | | 7x+8-x+7=3x+24 | | (x-3)2=15 | | -24=t-29 | | 40-13x=1 | | x^2-4x+6y+10=0 | | 8.5(13x-27)=-119 |